2019
DOI: 10.7555/jbr.32.20170057
|View full text |Cite
|
Sign up to set email alerts
|

Atypical chemokine receptor CCRL2 is overexpressed in prostate cancer cells

Abstract: Atypical chemokine receptors have recently emerged as important molecular players in health and diseases; they affect chemokine availability and function and impact a multitude of pathophysiological events, including the tumorigenesis process. This family of atypical receptors comprises five members: ACKR1/DARC, ACKR2/D6, ACKR3/CXCR7, ACKR4/CCRL1, and ACKR5/CCRL2. This work evaluated the differential expression of these receptors in prostate cancer using quantitative PCR. Further evaluation of CCRL2 at the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Within the non-hematopoietic compartment, CCRL2 mRNA was detected in inflamed bronchial epithelium ( Oostendorp et al, 2004 ). Other reports described CCRL2 expression in hepatic stellate cells ( Zimny et al, 2017 ), in adipocytes ( Muruganandan et al, 2010 ), in skin ( Banas et al, 2015 ) and in different cancer tissues including breast ( Sarmadi et al, 2015 ) and prostate cancers ( Reyes et al, 2017 ). In primary human endothelial cells, either derived from umbilical veins, dermal microvascular or brain vasculature, CCRL2 was significantly upregulated by proinflammatory stimuli (e.g., the combination of LPS, IFN-γ, and TNF-α) ( Monnier et al, 2012 ).…”
Section: Regulation Of Ccrl2 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the non-hematopoietic compartment, CCRL2 mRNA was detected in inflamed bronchial epithelium ( Oostendorp et al, 2004 ). Other reports described CCRL2 expression in hepatic stellate cells ( Zimny et al, 2017 ), in adipocytes ( Muruganandan et al, 2010 ), in skin ( Banas et al, 2015 ) and in different cancer tissues including breast ( Sarmadi et al, 2015 ) and prostate cancers ( Reyes et al, 2017 ). In primary human endothelial cells, either derived from umbilical veins, dermal microvascular or brain vasculature, CCRL2 was significantly upregulated by proinflammatory stimuli (e.g., the combination of LPS, IFN-γ, and TNF-α) ( Monnier et al, 2012 ).…”
Section: Regulation Of Ccrl2 Expressionmentioning
confidence: 99%
“…CCRL2 expression was described in different cancer cells, including prostate and breast carcinoma, colorectal cancer liver metastasis and glioblastoma ( Yin et al, 2012 ; Wang et al, 2015 ; Akram et al, 2016 ; Reyes et al, 2017 ). However, the functional role of CCRL2 in cancer is still unknown and needs further investigations.…”
Section: Role Of Ccrl2 In Tumorsmentioning
confidence: 99%
“…CCRL2 expression was also detected in colorectal cancer, where increased already in the early phase of liver colonization, what suggests involvement of the receptor in tumor metastatic processes [341]. In addition, CCRL2 is overexpressed in a metastatic prostate cancer cells and prostate cancer tissues from patients, both at the mRNA and protein level [342]. Moreover, CCRL2 showed cytoplasmic staining in examined cell line PC-3.…”
Section: Ccrl2/ackr5mentioning
confidence: 92%
“…ACKRs typically bind chemokines without G protein signalling activation to promote ligand internalization and degradation; however, more importantly, they regulate immune functions by scavenging chemokines from the local environment. 32 Previous studies have demonstrated CCRL2 receptors to act as decoy receptors scavenging chemokines from the TME and their expression to be associated with poor dendritic cell trafficking. 33 Elevated CCRL2 expression has been shown in primary neutrophils relative to other immune cell types and further upregulated on neutrophil activation.…”
Section: Differential Tumour Immune Cell Infiltration Immune-related Differentially Expressed Genes Patient Outcomes In Cortisol-secretinmentioning
confidence: 99%